Lithium-enriched graphite anode surfaces investigated using nuclear reaction analysis. Issue 93 (6th November 2020) - Chebuske, Matthew; Higashiya, Seiichiro; Flottman, Spencer; Bakhru, Hassaram; Antonopoulos, Byron; Paschos, Odysseas; Gittleson, Forrest S.; Efstathiadis, Harry
Abstract : Non-destructive Li nuclear reaction analyses were used to profile the Li distribution at the surfaces of graphitic Li-ion battery anodes. Abstract : Non-destructive Li nuclear reaction analysis techniques were used to profile the Li distribution at the surface of graphitic Li-ion battery anodes. These techniques show that Li concentrations are elevated within 300 nm of the anode surface, even in fully delithiated states. The surface region, which includes the solid electrolyte interphase, contains at least 60% of the total Li irreversibly lost during formation and cycling.